Critical issues in current climate policy: Hot air, multi-level emission trading registries and changes in emission commitments due to international conflicts - Axel Michaelowa; Tobias Koch (Hamburg Institute of International Economics (HWWA), 1999)
Currently, international climate negotiations concentrate on design issues for the flexible instruments outlined in the Kyoto Protocol. As the 6th Conference of the Parties to the U.N. Framework Convention on Climate Change in late 2000 or early 2001 has to take decisions on these matters, it is imperative to develop solutions that combine long-term economic efficiency with long-term environmental effectiveness. Sometimes, a reconciliation of these targets is difficult and compromises have to be made. This report discusses solutions for three critical issues which have got different degrees of attention until now but are linked inasmuch their solution will be crucial for the success of the Kyoto Protocol. The authors have come across them due to their close involvement in the negotiation process. The first issue has been a major topic of debate - the possibility that Russia and other countries in transition may have an enormous surplus of emission permits due to their economic collapse. Unfettered trade in this surplus would artificially depress permit prices, reduce the incentive for long-term innovation and would not be linked to any efficiency improvement in the selling countries. Koch and Michaelowa discuss ways how incentives can be devised to link sales of emission permits with actions that lead to long-term emission reductions. They include an element of early action designed to prevent lock-in on an emission-intensive path of economic recovery by fostering investments whose emission reduction cannot be quantified but is nevertheless real. Early project-related Joint Implementation plays an important role in this context. The second issue is relatively technical but a necessary condition for the functioning of a global market in emission permits. It deals with the design of a system of national registries that track trades in permits. An International Registry would be the node of this system and guarantee that no fraudulent trades enter the system. A homogenous trading unit would be created. The way how trades are processed, the information requirements and the time-related aspect of the implementation of the registry system are discussed. Finally, the third issue seems remote but may prove challenging in the long term. International conflict will impact upon the Kyoto Protocol commitments. Wars like the one in Kosovo will lead to additional greenhouse gas emissions that have to be accounted for. Territorial changes will lead to changes in commitments. The authors discuss the different possibilities that change commitments and make recommendations how they could be accommodated in the Kyoto framework. Dr. Axel Michaelowa, a former staff member of HWWA Institute for Economic Research, is now working as an independent climate policy expert in Paris. Among other functions, he serves as a permanent advisor and project coordinator for HWWA on the economics of international climate policy. Tobias Koch is a specialist on Russian climate and energy policy. He is doing research with the Center for Energy Policy in Moscow and has also worked for the UN climate change secretariat on issues of emissions trading. However, the views expressed in this report are his personal ones.
Keywords: 330; Klimaschutz; Luftreinhaltung; Kohlendioxid; Internationale Umweltpolitik; Internationaler Transfer; Russland